Structural style and tectonic evolution model, Pisco Este Basin, offshore - Peru - Peña Sierra, Fernando Daniel (2023)
The East Pisco basin belongs to the group of basins of the Peruvian forearc. This basin has been studied based on the description and interpretation of excellent outcrops along the coast. the East Pisco basin in its offshore area is characterized by a complex tectonic history which has been interpreted in this study with subsurface information (2D-3D seismic) and integrated with the geological information of the coastal sector. This paper shows the interpretation of seismic horizons corresponding to stratigraphic units, the main fault, and folding systems. The main structural styles of the basin are determined, and a model of tectonic evolution is proposed.